2013
DOI: 10.7567/jjap.52.061002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoluminescence from InGaN/GaN Quantum Wells on A GaN/Si(111) Template with Extended Three-Dimensional GaN Growth on Low-Temperature AlN Interlayer

Abstract: This paper describes a low-cost route for the reduction of dislocations during growth of GaN on Si(111) using metalorganic vapour phase epitaxy (MOVPE) through three-dimensional (3D) island growth on a low temperature AlN layer which introduces a compressive stress into the over-lying GaN layer to compensate for the thermal mismatch stress between the nitride layer and Si(111) substrate. Such a 3D growth process leads to the reduction of grain twist as the result of the reduction in the number of dislocations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…24 Jiang et al showed that GaN tends to grow in 3D mode on a non-annealed AlN interlayer, but in 2D mode on an annealed AlN interlayer. 26 In addition to the thickness of the AlN interlayer and the post-growth annealing thermal treatment, the AlN interlayer growth temperature is also one of the most important parameters that affects the structural properties of the AlN interlayer. However, the precise role of the AlN interlayer growth temperature on the 3D GaN growth and the quality of GaN epitaxial films is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…24 Jiang et al showed that GaN tends to grow in 3D mode on a non-annealed AlN interlayer, but in 2D mode on an annealed AlN interlayer. 26 In addition to the thickness of the AlN interlayer and the post-growth annealing thermal treatment, the AlN interlayer growth temperature is also one of the most important parameters that affects the structural properties of the AlN interlayer. However, the precise role of the AlN interlayer growth temperature on the 3D GaN growth and the quality of GaN epitaxial films is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Raman spectra of sample 1 are further away from the dashed line in comparison with those of sample 2. Therefore, sample 1 has a high level of tensile stress and it is not surprising that cracks have been observed [9]. In summary, this approach provides a better characterization method compared to conventional Raman spectroscopy by comparing figures 6 and 7 with figure 5.…”
Section: Raman Spectra With Positionmentioning
confidence: 92%
“…The structures were also treated with SiH 4 to reduce the dislocation density. For sample 1, extensive three dimensional (3D) GaN island growth on the LT AlN interlayer was demonstrated for the reduction of dislocations [9]. The Si dopant concentration is estimated to be ∼5-7 × 10 +18 cm −3 in Si:GaN layers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations